Mobile Technology Use of Junior High School Students (Ascendens Asia Singapore – Union Christian College Philippines Journal of Multidisciplinary Research Abstracts, 2026)
The study utilized quantitative descriptive design to gather data from 102 Junior High School students using a survey questionnaire. Weighted mean was used to describe their mobile technology use along the stated purposes, and the difference in their use when they are grouped according to their profile.The findings revealed high levels of mobile technology use along the three purposes. Notably, the respondents use mobile technology more extensively for entertainment purposes, primarily utilizing it to listen to music and taking pictures of any occasion. It is followed by learning purposes, using it to search for video learning materials, and generating ideas for their academic requirement. Finally, under utility purposes, they utilize it for recording audio, videos, and taking pictures, and browsing the internet in general. Moreover, there is a significant difference in learning purposes between male and female, where the former tend to use it more than the latter. Furthermore, there is a significant difference in the use under learning purposes between Grade 9, and Grade 7 and 8. Overall, this study provides valuable insights and information into the mobile technology use which can be useful in understanding their needs. The researchers recommend that advocacy plans be done to elevate their use of these technologies to become more productive and improve wellbeing.
Keywords: mobile technology use; educational technology; technological wellbeing